PENGARUH TINDAKAN SUPERVISI, BUDAYA ORGANISASI, KEPRIBADIAN, DAN PELATIHAN TERHADAP KELENGKAPAN LAPORAN KEUANGAN Studi pada Kabupaten Karanganyar - Anwar, Desiandi Sayful; Amalia, Dewi (JURNAL AKUNTANSI DAN AUDITING, 2010)
This study empirically examined the influence of the supervising, culture, personality, and training on the completeness of financial statements of the local governments. To collect the data, a research instrument was prepared to participant. Using survey information collected from 50 accountant who prepare the financial statement on Kabupaten Karanganyar Central Java Province, this study uses full regression method. The results of the test show that the supervising and training provide influence on the completeness of financial statements on Kabupaten Karanganyar. The results indicated that the supervising from the higher managers increase the financial statements completeness. And in the same way, training for the accountant increase the completeness of financial statements too.However, the researcher failed to find the influence of the culture and personality on the completeness of financial statements of the local governments.